2010
DOI: 10.1007/s10722-010-9623-z
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic and natural causes influencing population genetic structure of Juniperus procera Hochst. ex Endl. in the Ethiopian highlands

Abstract: Juniperus procera is economically highly important but threatened tree species. It is the only species among 67 taxa in the genus Juniperus that naturally grows in Africa and south of the equator extending up to 18°S in Zimbabwe. Ethiopia is assumed to host the largest J. procera populations, which are also believed to have high genetic variation owing to their wide ecological amplitude. This study assessed genetic variation at AFLPs of J. procera populations in the Ethiopian highlands. In the study six popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 47 publications
2
8
2
Order By: Relevance
“…The lowest pairwise genetic distance which was realized between Menagesha-Suba and Wef-Washa may confirm the historical record that claims Menagesha-Suba as plantation of wildlings from Wef-Washa back in 15 th century [42,43]. These two populations were also the only undifferentiated pairs in AFLP analysis of the six populations [44]. The low differentiation between Chilimo and Yabelo, however; is contrary to the one reported by [44] between which the authors computed the highest differentiation.…”
Section: Population Genetic Variationsupporting
confidence: 59%
See 1 more Smart Citation
“…The lowest pairwise genetic distance which was realized between Menagesha-Suba and Wef-Washa may confirm the historical record that claims Menagesha-Suba as plantation of wildlings from Wef-Washa back in 15 th century [42,43]. These two populations were also the only undifferentiated pairs in AFLP analysis of the six populations [44]. The low differentiation between Chilimo and Yabelo, however; is contrary to the one reported by [44] between which the authors computed the highest differentiation.…”
Section: Population Genetic Variationsupporting
confidence: 59%
“…These two populations were also the only undifferentiated pairs in AFLP analysis of the six populations [44]. The low differentiation between Chilimo and Yabelo, however; is contrary to the one reported by [44] between which the authors computed the highest differentiation. The result in this study is likely due to the allele size 155 bps at Jc-31 which was shared between the two populations at higher frequency.…”
Section: Population Genetic Variationcontrasting
confidence: 55%
“…Similarly, in a study performed by Sertse et al . (), it has been suggested that the Great Rift Valley acts as a natural barrier for gene flow for Juniperus procera Hochst. ex Endl.…”
Section: Discussionmentioning
confidence: 99%
“…The Menagesha-Suba forest currently comprises a 2667.6 ha of natural forest and 2783.7 ha of plantation forest. Menagesh suba forest was once a grass land or farmland before the then king Zeray yacob (1597-1603) ordered its reforestation by using J. procera seeds originating from Wof-Washa forest (Alemayehu et al, 2009;Sertse et al, 2011). Now the forest has matured into, according to Friis et al (2010), a kind of undifferentiated afromontane forest with canopy of J. procera and P. falcatus.…”
Section: Description Of the Study Areamentioning
confidence: 99%